Illustrating the Components of Professional Self-Awareness through Reflexive Essay - Y. V. Lazareva (Научный диалог)
The article is devoted to the study of the degree of formation of professional self-consciousness of students of psychological and pedagogical areas of training, the third year of study. The relevance of the study is determined by the search for approaches that contribute to the effective formation of general professional and special professional competencies, development of professionally significant qualities, development of professional self-consciousness. The article contains a review of scientific results aimed at the study of “self-consciousness” and “professional self-consciousness” of the person. Definitions for such phenomena as “vocational teacher education,” “identity,” “professional identity” are given. Special attention is paid to the structure of professional self-consciousness, the content and specificity of each component is considered in detail. An important part of the article is the analysis of the content of reflexive essays by students, future teachers, psychologists, on the topic “My life in the profession as I see it.” Excerpts from the essay illustrating the manifestations of cognitive, affective, behavioural components of professional self-consciousness are given. Much attention is paid to the consideration of the elements of the cognitive component, namely professional I-image, transformed by the time criterion - past, present and future. The conclusions fix the relations between the experience of teaching at the stage of self-determination, confidence in own capabilities in the learning process and motivation for positive professional changes in the future.